Book Review: Ngā Tai Matatū: Tides of Māori Endurance - Waetford, Tane (Victoria University of Wellington Law Review, 2005)
This article is a book review of Mason Durie Ngā Tai Matatū: Tides of Māori Endurance (Oxford University Press, Melbourne, 2005) (288 pages). Māori have faced many challenges that have threatened their way of life and tested their ability to adapt to new and changing circumstances. This book examines the many events that have shaped and influenced Māori life and analyses the way in which Māori have responded to such challenges. Waetford states that the analysis provides a valuable insight into Māori aspirations and values and provides a framework for future development. The book considers the way forward for Māori by looking at the position of Māori at the beginning of the third millennium and the challenges that lie ahead.